Education and psychology trends: impact on information literacy - Sanches, Tatiana (2018)
This chapter describes the trends in Education and Psychology which have an impact on Information Literacy. Based on a literature review, it provides a comprehensive view of these trends and of the expectations thereof with regard to three aspects: the relationship between education, learning and higher education; information behavior, emotions, perception and cognition, in a social and individual context; and finally technologies, virtual environments and digital information that impact libraries and their services.